Usability assessment of E-commerce systems using McCall’s quality model - Siti Solehah, Othman; Noraziah, Ahmad; Roslina, Mohd Sidek (Science Publications, 2025)
E-commerce platforms rely fundamentally on business database transaction systems that must balance user experience with security and data integrity. Traditional usability assessment methodologies often overlook critical security elements and transactional integrity requirements. This study employs McCall's Quality Model to comprehensively evaluate the usability characteristics of three prominent e-commerce platforms: Temu, Shopee, and Lazada. Through structured task-based evaluations and Likert-scale questionnaires, eight quality factors were assessed: Correctness, Reliability, Efficiency, Integrity, Usability, Maintainability, Flexibility, and Testability. Thirty participants aged 20-40 years with varying levels of e-commerce experience completed the evaluation protocol. Data reliability was confirmed using Cronbach's Alpha, while Analysis of Variance (ANOVA) identified statistically significant differences across platforms. Results demonstrate that Shopee excels in most usability subcategories, particularly in Integrity and Usability, reflecting superior security implementation and user-centered design. The findings provide actionable recommendations for platform developers to enhance usability while strengthening transactional security mechanisms. Specifically, the study proposes improvements to checkout procedures, navigation architecture, and system performance optimization. By integrating security-critical factors into usability assessment, this research addresses a significant gap in existing evaluation frameworks that traditionally prioritize user satisfaction metrics over transactional integrity. The study concludes by advocating for AI-driven usability testing methodologies that enable automated user interaction analysis and real-time bottleneck identification in future e-commerce platform evaluations.